2010
DOI: 10.1097/pcc.0b013e3181ae5a4c
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant phospholipids, surfactant proteins, and inflammatory markers during acute lung injury in children

Abstract: Changes to the phosphatidylcholine profile, surfactant proteins, and inflammatory markers of bronchoalveolar lavage fluid and plasma in children with acute lung injury are consistent with an alveolar/blood leakage and inflammatory cell membrane degradation products. These changes are due to alveolar capillary membrane damage and cellular infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 38 publications
4
46
0
1
Order By: Relevance
“…A previous study performed in adults with pneumonia, ARDS, or cardiogenic edema showed that in adults with pneumonia the BALF PL and phosphatidylcholine (PC) content were not significantly different compared with controls (2). It is conceivable that the TAs unsaturated-PC derived from inflammatory cells may have contributed to mantain the same amount of TAs PL content in our newborns with pneumonia together with the increase of other surfactant PL classes, either than the sole DSPC (13). Regarding SP-A (%PL) ratio, Dargaville et al (10) expressed SP-A content as weight/volume of ELF, and as opposed to our study, they found that ELF SP-A in infants with respiratory syncytial virus bronchiolitis was, at the peak of the disease, significantly lower compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study performed in adults with pneumonia, ARDS, or cardiogenic edema showed that in adults with pneumonia the BALF PL and phosphatidylcholine (PC) content were not significantly different compared with controls (2). It is conceivable that the TAs unsaturated-PC derived from inflammatory cells may have contributed to mantain the same amount of TAs PL content in our newborns with pneumonia together with the increase of other surfactant PL classes, either than the sole DSPC (13). Regarding SP-A (%PL) ratio, Dargaville et al (10) expressed SP-A content as weight/volume of ELF, and as opposed to our study, they found that ELF SP-A in infants with respiratory syncytial virus bronchiolitis was, at the peak of the disease, significantly lower compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Only two reports have previously described surfactant composition changes during bacterial pneumonia in infants (12,13). Both studies corrected the TA dilution by TA total protein amount; this method is less reliable than the ELF method because of the risk to underestimate the SPs amounts due to the increased alveolar capillary leak during the disease's course (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other cross-sectional cohort study, Todd et al also have shown that SP-D is increased in both BAL and plasma during ALI and that there was significant increase in SP-D breakdown products in the lungs of these patients [78]. The elevated BAL SP-D level was also associated with respiratory dysfunction, inflammation and increase in plasma SP-D and IL-8 levels during ALI [78]. However, an enhanced level of inflammatory markers, together with detection of significant amounts of SP-D breakdown products, during ALI raises the question about which of the pro- or anti-inflammatory forms of SP-D are elevated.…”
Section: 4 Sp-d In Human Studiesmentioning
confidence: 99%